2003
DOI: 10.1101/gad.1097903
|View full text |Cite
|
Sign up to set email alerts
|

Omi/HtrA2 catalytic cleavage of inhibitor of apoptosis (IAP) irreversibly inactivates IAPs and facilitates caspase activity in apoptosis

Abstract: Omi/HtrA2 is a mitochondrial serine protease that is released into the cytosol during apoptosis to antagonize inhibitors of apoptosis (IAPs) and contribute to caspase-independent cell death. Here, we demonstrate that Omi/HtrA2 directly cleaves various IAPs in vitro, and the cleavage efficiency is determined by its IAP-binding motif, AVPS. Cleavage of IAPs such as c-IAP1 substantially reduces its ability to inhibit and ubiquitylate caspases. In contrast to the stoichiometric anti-IAP activity by Smac/DIABLO, Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(221 citation statements)
references
References 36 publications
8
206
2
3
Order By: Relevance
“…The Omi/HtrA2-mediated proteolytic cleavage might inactivate and remove antiapoptotic molecules, as has been shown for IAPs, 8,9 or it might be required for activation of precursor proteins whose function might be necessary for the caspase-independent neutrophil cell death. Since this type of cell death has been suggested to be mediated by the mitochondria-derived reactive oxygen species (ROS), 5 it is logical to suppose that a mitochondrial antioxidant system, which normally inactivates an excess of ROS, is destroyed in this experimental setting.…”
Section: Dear Editormentioning
confidence: 89%
See 1 more Smart Citation
“…The Omi/HtrA2-mediated proteolytic cleavage might inactivate and remove antiapoptotic molecules, as has been shown for IAPs, 8,9 or it might be required for activation of precursor proteins whose function might be necessary for the caspase-independent neutrophil cell death. Since this type of cell death has been suggested to be mediated by the mitochondria-derived reactive oxygen species (ROS), 5 it is logical to suppose that a mitochondrial antioxidant system, which normally inactivates an excess of ROS, is destroyed in this experimental setting.…”
Section: Dear Editormentioning
confidence: 89%
“…However, it has been shown that in 293 cells transfected with the active site mutant Omi/HtrA2, which had no protease activity, caspase activation and cell death were markedly diminished, whereas transfection of the wild-type protein induced both events and resulted in significant reduction in the amount of XIAP in the transfected cells, which appeared to be a substrate of Omi/ HtrA2. 8,9 Obviously, the way Omi/HtrA2 participates in cell death may differ in various cell types.…”
Section: Dear Editormentioning
confidence: 99%
“…It was reported that SMAC is overexpressed in several types of solid tumors such as colon, stomach, prostate, ovary, and lung cancers [73]. Likewise, HtrA2/Omi delivery is triggered via apoptotic induction and then, it binds to IAPs through its IAP-binding motif (IBM) [74]. XAF1, the other potent IAP antagonist, binds to BIR domains of IAPs such as XIAP, cIAP1, and cIAP2 and by this way, promotes apoptosis [75].…”
Section: Inhibitors Of Apoptosis Proteins and Inhibitors Of Apoptosismentioning
confidence: 99%
“…8 In addition, the mitochondrial serine protease Omi/HtrA2 has been shown to facilitate caspase-9 activation by disrupting inhibitor of apoptosis protein (IAP) inhibition of caspase-9 9-11 and degrading IAPs. 12,13 TNF signals through two receptors, tumor necrosis factor receptor (TNF-R) 1 and TNF-R2. Signaling through TNF-R1 14,15 activates both prosurvival signals including NFkB and Jun N-terminal kinase as well as proapoptotic signals.…”
Section: Introductionmentioning
confidence: 99%